Strengthening Religious Moderation through the Local Wisdom Values ​​of Sipakatau, Sipakalebbi, and Sipakainge in Islamic Religious Education - Arifin, Ince Ansar H; Amri, Ulil; Yusuf, Muhammad; Tang, Muhammad (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the role of the local wisdom values of Bugis Sipakatau, Sipakalebbi, and Sipakainge in strengthening religious moderation through Islamic Religious Education (PAI). Using a qualitative approach through the library research method, this study examines relevant literature related to the concept of religious moderation, Islamic education, and local Bugis cultural values. The results of the study show that the three main values are closely related to Islamic principles that emphasize humanity, justice, and balance in religion. Sipakatau means humanizing humans, Sipakalebbi emphasizes mutual respect, while Sipakainge contains the value of reminding each other in kindness. These three values substantively reflect the principles of religious moderation, namely fairness, tolerance, and avoiding extremism. The implementation of 3S values in PAI learning can be carried out through contextual and culture-based approaches, such as social projects, reflection on human values, and collaboration with indigenous leaders and local scholars. This study concludes that the integration  of Sipakatau, Sipakalebbi, and Sipakainge values  not only strengthens the relevance of PAI in the multicultural context of Indonesia, but also becomes a strategic foundation for building a religious character that is moderate, humanist, and rooted in the nation's culture.